2020
DOI: 10.3390/molecules25132998
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Antagonist UFR2709 Inhibits Nicotine Reward and Decreases Anxiety in Zebrafish

Abstract: Zebrafish is becoming a popular animal model in neuropharmacology and drug discovery, mainly due to its ease of handling and low costs involved in maintenance and experimental work. This animal displays a series of complex behaviours that makes it useful for assessing the effects of psychoactive drugs. Here, adult zebrafish were used for assessment of the anxiolytic and anti-addictive properties of UFR2709, a nicotinic receptor (nAChR) antagonist, using two behavioural paradigms to test for addiction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…This behavioral paradigm has been previously validated by many labs to test the anxiolytic-like effects of compounds, such as nicotine, fluoxetine, diazepam, buspirone, chlordiazepoxide, and tranylcypromine [ 5 , 6 , 10 , 14 , 18 , 22 , 25 , 26 , 29 , 30 , 32 , 36 , 37 , 39 , 44 , 50 , 53 , 57 59 , 66 ]. In fact, regulation of this anxiety-like behavior by nicotine and other nicotinic ligands has been reported in several publications, supporting the pharmacological relevance of nAChR in zebrafish anxiety [ 5 , 28 , 32 , 33 , 53 , 67 ].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…This behavioral paradigm has been previously validated by many labs to test the anxiolytic-like effects of compounds, such as nicotine, fluoxetine, diazepam, buspirone, chlordiazepoxide, and tranylcypromine [ 5 , 6 , 10 , 14 , 18 , 22 , 25 , 26 , 29 , 30 , 32 , 36 , 37 , 39 , 44 , 50 , 53 , 57 59 , 66 ]. In fact, regulation of this anxiety-like behavior by nicotine and other nicotinic ligands has been reported in several publications, supporting the pharmacological relevance of nAChR in zebrafish anxiety [ 5 , 28 , 32 , 33 , 53 , 67 ].…”
Section: Introductionsupporting
confidence: 52%
“…Many publications now support the suitability of zebrafish to model various aspects of anxiety-related states [ 26 , 30 , 58 ]. In fact, zebrafish NTT has been validated using several clinical anxiolytic compounds, including buspirone, fluoxetine, diazepam, chlordiazepoxide, and tranylcypromine [ 5 , 6 , 10 , 14 , 18 , 22 , 25 , 26 , 29 , 30 , 32 , 36 , 37 , 39 , 44 , 50 , 53 , 57 59 , 66 ] and has also shown to be sensitive to nicotine and other nicotinic ligands [ 5 , 28 , 32 , 33 , 53 , 67 ]. In this study, we investigated the effects of nicotine and six additional nAChR-activating alkaloids on the NTT.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Viscarra F et al, reported there was no big difference in β-actin expression among the control and the stressed fish. Using standard RT-PCR, the level of mRNA expression of α4 nACh and α7 nACh receptor subunits in the brain of adult zebrafish exposed with net stressor was determined and found the level of expression of α4 and α7 receptor subunit of mRNA were significantly reduce [87]. Cytokines are important brain mediators in neuromodulation, and they are especially useful for investigating modelling psychological effects [88,89].…”
Section: Gene Expressionmentioning
confidence: 99%
“…The α4β2 subtypes, which are the major nAChRs present in the central nervous system (CNS) [ 6 , 7 ] have been proposed as the principal subtypes involved in anxiety and nicotine addiction; however, another nAChR subtype could contribute to these disorders. The nAChR subtypes have been studied in different animal models such as non-human primates, cats, frogs, rats, mice, and zebrafish, associated with different behaviors such as memory loss and drug abuse, among others, and play a key role in the anxiolytic activity of nicotine [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its versatility in development and the number of individuals for experimentation make the zebrafish an appropriate animal model for studying new drugs [ 20 , 21 ]. Behavioral studies have been used with zebrafish in complex paradigms related to memory, anxiety, stress, addiction, and the reinforcing properties of drug abuse [ 11 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%